2018
DOI: 10.1017/s0029665118000770
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of B-vitamin supplementation on neuropsychiatric performance: results from the BrainHOP trial

Abstract: Globally populations are ageing and mental health disorders, including dementia and depression, are reported as the leading cause of disability and ill health in older people (1). Epidemiological and randomised trial evidence supports potential roles for folate and the metabolically related B-vitamins in preventing cognitive dysfunction and depression in ageing, but the evidence is inconsistent (2). The aim of this study was to investigate the effect of supplementation with folate and related B-vitamins, over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Of these, one was a quasi-experimental pre-test-post-test control group design [22], one was a placebo-controlled trial allocated on matching principle [23], and the others were randomized, placebo-controlled designs. Two were letters to the editor [24,25], one was printed in proceedings [26] and the others were full articles formally published in journals. Sample sizes ranged from 22 to 1053.…”
Section: B Vitaminsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, one was a quasi-experimental pre-test-post-test control group design [22], one was a placebo-controlled trial allocated on matching principle [23], and the others were randomized, placebo-controlled designs. Two were letters to the editor [24,25], one was printed in proceedings [26] and the others were full articles formally published in journals. Sample sizes ranged from 22 to 1053.…”
Section: B Vitaminsmentioning
confidence: 99%
“…As for the dosage and ingredient of B vitamin supplementation, 13 studies reported the use of folate (400 to 5000 µg), vitamin B6 (3 to 50 mg), and vitamin B12 (20 to 1000 µg) simultaneously [22][23][24]26,[28][29][30][32][33][34][35][36][37], with two of them using riboflavin as well (10 and 25 mg, respectively) [26,29]. Four studies used folate (400 to 5000 µg) and vitamin B12 (25 to 1500 µg) concurrently [27,[38][39][40].…”
Section: B Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding B Complex vitamins, we included a total of 14 studies. In total, eight of them compared B Complex vitamins to placebo [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], five of them compared B Complex vitamins to conventional treatment [ 45 , 46 , 47 , 48 , 49 ], and one compared vitamin B supplementation with vitamin C supplementation [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mean FAB and RBANS scores before and after treatment in intervention and control groups[44]. Participants inMa F. et al.…”
mentioning
confidence: 99%